"Sitolu Sada": A Music Composition Based on The Cultural Values of Dalihan Na Tolu - Tria Amelia Simbolon; Mauly Purba; Vanesia Amelia Sebayang; Shafa'atussara Silahudin (Gondang: Jurnal Seni dan Budaya, 2026)
The musical composition Sitolu Sada was created by adopting the concept of “triadic unity” found in the cultural system of Dalihan Na Tolu. The composer chose this triadic concept because the Batak Toba community is deeply rooted in the symbolism of threes. This triadic principle is not only present in Dalihan Na Tolu, but also in Debata Na Tolu, Banua Na Tolu, and Bonang Manolu, all of which are important elements of Batak mythology. The concept of three is embedded into the structure of the music—reflected in its rhythm, meter, key signatures, timbre, harmony, and more. This composition highlights traditional Batak Toba musical values while incorporating elements of Western music. Sitolu Sada was developed using Alma Hawkins’ creative process methodology, which involves three main stages: exploration, improvisation, and composition. The composer went through several phases—from the initial idea to a fully realized musical performance. These stages include ideation, the creative process (exploration, improvisation, composition), presentation in performance form, and interpretation by musicians from notation to sound, ultimately making it accessible to listeners. The composition Sitolu Sada consists of three movements: Sitolu Sada I, Sitolu Sada II, and Sitolu Sada III. Through the creation of this work, it is hoped that the complexity of Dalihan Na Tolu can be appreciated and expressed as a creative outcome grounded in local wisdom and the rich values it represents.